The Upper Buccal Musculomucosal Flap for Nasal Lining and Columellar Defect Reconstruction. Issue 5 (July 2021) - Yen, Cheng-I; Chang, Chun-Shin; Chen, Hung-Chang; Yang, Shih-Yi; Chang, Shu-Yin; Yang, Jui-Yung; Chuang, Shiow-Shuh; Hsiao, Yen-Chang
Abstract : Abstract: Restoring the nasal lining is a great challenge in the reconstruction of nasal defects. In this series, the authors present our experience in using the upper buccal musculomucosal (UBMM) flap for the reconstruction of full thickness columellar or nasal lining defects. Ten patients who underwent UBMM flap reconstruction of columellar or nasal lining defects, with or without composite grafting, were identified between December of 2014 and February of 2017. The records were retrospectively reviewed to determine the demographics, nasal deformity etiology, surgical technique, complications, flap survival rate and duration of follow-up. Of these ten patients, three were men, and seven were women; the average age was 48.1 years (range, 34–66 years). Four patients underwent bilateral UBMM flaps, and 6 patients underwent unilateral UBMM flap reconstruction. All of the donor sites were closed without complications, except for one small granuloma that occurred 8 months later. Of the total 14 flaps, 7 healed well, 6 healed well after minimal debridement in the clinic, and one failed and was replaced with a contralateral UBMM flap. The average follow-up time was 20.1 months (range, 8–38 months). All patients had satisfactory aesthetic and functional outcomes. Due to the limited availability of healthy local tissue for nasal lining reconstruction after multiple surgeries, the UBMM flap serves as an applicable choice to restore columellar or nasal lining defects, with minimal donor site morbidity and no visible external scarring. Abstract : Supplemental Digital Content is available in the text